If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + 2(6 + 7x) = -93 -7 + (6 * 2 + 7x * 2) = -93 -7 + (12 + 14x) = -93 Combine like terms: -7 + 12 = 5 5 + 14x = -93 Solving 5 + 14x = -93 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 14x = -93 + -5 Combine like terms: 5 + -5 = 0 0 + 14x = -93 + -5 14x = -93 + -5 Combine like terms: -93 + -5 = -98 14x = -98 Divide each side by '14'. x = -7 Simplifying x = -7
| 4b+3b-5=16 | | 2x^3+x+9=0 | | 8x+5=3x | | 8t^2=0 | | 8n-(1-4n)=-85 | | 6t^2+37t-35=0 | | v^2-7v+6=0 | | -4.9x^2+80x=0 | | 3x+24=72 | | 9.7=x+4.3 | | 18+x=42 | | 5x^4-80y^4=0 | | 5x^2-45+90=0 | | 5x^4-16y^4=0 | | 252=-r+5(6r+4) | | 12n=84 | | 3m+15=m+30 | | -5a(3a^2-6a)-4(2a^2-4a)=0 | | 27x^3-75xy^2=0 | | 3y-8=7-2y | | 0.11x+0.12(x+4000)=940 | | x^4-3x^3+8x-2=0 | | 9a^2-49b^4=0 | | 1x+1.7x+2x=100 | | y-5=0.3y+4.1 | | 6x^2y+9xy^2z+3xyz=0 | | 3(4x-2)-(5x-8)=8-(2x+3) | | 4x+8x-2+x=360 | | -x-5+2x=0 | | 9.29x-280=0 | | 10-7y=3 | | 12x^5y+8x^3y^2=0 |